Think of Lampedusa - Guébo, Josué, 1972- (African poetry book, 2017)
"A collection of serial poems, Think of Lampedusa addresses the 2013 shipwreck that killed 366 Africans attempting to migrate secretly to Lampedusa, an Italian island in the Mediterranean Sea. The crossing from North Africa to this island and other Mediterranean way stations has become the most dangerous migrant route in the world. Interested in what is producing such epic displacement, Josue Guebo's poems combineelements of history and mythology. Guebo considers the Mediterranean not only as a literal space but also as a space of expectation, anxiety, hope, and anguish for migrants. Hemeditates onthe long history of narratives and bodies trafficked across the Mediterranean Sea. What did it--and what does it--connect and separate? Whose sea is it? Ultimately he is searchingfor what motivates a person to become part of what he calls a "seasonal suicide epidemic." This translation of Guebo's Songe à Lampedusa, winner of the Tchicaya U Tam'si Prize for African Poetry, is a searing work from a major African poet."--